Orthographia, Arithmetica e Siencias. Três tratados do P.e António Pessoa, S. J. (c. 1648) - Armando, Martins (2023)
This chapter intends to analyze the manuscript of the Public Library of Évora (BPE Maniz. cod. 99) Orthographia practica, Arithmetica, Sciencias, focusing on the relation between the Latin texts (emblems, mottoes, epigrams...) and the iconographic elements. It is demonstrated that António Pessoa appropriates images and mottoes from scattered printed sources (Stradanus, Plantin, Icíar...), but casts them into a coherent whole articulated around three thematic nodes: (1) expressions of faith and devotion consistent with Jesuit spirituality, (2) a political, educational program along the lines of the "mirror-for-princes" literature, (3) the assertion of the author's competence both as calligrapher and draughtsman. A Portuguese translation of the Latin epigrams present in the manuscript, as well as the translation of a Latin epigram of the 1550 edition of Icíar's Arte Subtilissima.